A comprehensive review on BLDC motor and its control techniques. (20th August 2021) - Kumar, Dileep; Gupta, R.A.
Brushless direct current (BLDC) motor drives have gained more popularity and emerged as a latest research area due to their ability to offer salient features such as compact size, higher efficiency, less maintenance, rugged operation, more reliable, and high torque to weight ratio. Recently, BLDC motor drives are widely adopted in numerous fields of industries and household applications such as robotics, electric vehicle, defence, aviation, industry, ventilation, dryer, and refrigerators. Moreover, rectangular phase currents are required to produce constant torque. However, practically, rectangular current cannot be obtained due to phase-winding inductance. Therefore, BLDC motor drives are facing great challenge of current ripples due to the unequal rate of incoming and outgoing phase current during the commutation process. In view of these aspects, this paper presents a comprehensive review on BLDC motor drive. Different converter topologies and current/torque control techniques are carried out to verify potential of BLDC motor drives.